Research Activities of the IMF, January 1991-December 1999. (Pamphlet Series; Pamphlet Series, No., 2000)
Research activity in the IMF emphasizes the links between the organization's policy and operational concerns. The main objectives of research is IMF staff understanding of policy and operational issues relevant to the institution, and to improve the analytical quality of the work prepared for management and the Executive Board and the advice provided to member countries. The scope of research in the IMF is defined by the purposes and functions of the institution. In order to foster innovation and ensure quality control, the IMF makes much of its research available outside the institution and encourages staff to interact with academia and other research organizations through conferences, seminars, and occasional joint research projects. The visiting scholar's program has also enhanced the quality of research done in the IMF. This program brings in leading members of the economics profession from around the world to assist in the preparation of papers for the Executive Board and to conduct research on IMF-related issues.